Efektivitas Program Sleep Hygiene Berbasis Sekolah–Keluarga terhadap Kesehatan Fisik dan Psikologis Anak Sekolah Dasar - Eva Faradianti (Journal of Innovative and Creativity, 2025)
This study aims to evaluate the effectiveness of a school–family-based sleep hygiene program in improving sleep quality and overall well-being among Indonesian elementary school children. A quasi-experimental design was employed with intervention (n=90) and control (n=90) groups. Data were collected using the Sleep Disturbance Scale for Children, Pittsburgh Sleep Quality Index, Strengths and Difficulties Questionnaire, and actigraphy for objective triangulation. Findings indicated a significant increase in sleep duration (+42.3 minutes/night, p<0.01) and sleep efficiency (+6.8%), accompanied by improvements in emotional regulation (+14.2%) and prosocial behavior (+9.6%). Somatic complaints decreased by 22.4%, while illness-related absences were reduced by 1.2 days per student. Family compliance and school support were identified as key moderators of program success. Although BMI reduction was not statistically significant, the positive trend suggests long-term metabolic benefits. These results confirm the effectiveness of multilevel school–family interventions in enhancing children’s physical and psychological health, contributing empirical evidence from Southeast Asia to inform culturally grounded, preventive health education policies in Indonesia.